Effect of Homogenous Ceramic Waste on Drying Shrinkage of Mortar - Abdul Shukor Lim, Nor Hasanah; Samadi, Mostafa; Shafegat, Arezou; Nur Farhayu, Ariffin; Keyvanfar, Ali; Mohd. Sam, Abdul Rahman (Journal of Environmental Treatment Techniques, 2016)
Concrete has become important building material in the construction industry due to its mechanical and physical properties. However, large needs of concrete usage lead to the depletion of natural resources. Therefore the use of industrial by-product has been given attention. Ceramic materials are largely used worldwide and consequently, produced large amount of waste from the tile manufacturers and construction industry. These wastes were dumped in landfills and not recyclable. This study investigates the effect of ceramic powder as cement replacement and ceramic fine aggregates as sand replacement on the strength development and drying shrinkage of the mortar. The cement was replaced by 40% ceramic powder by weight of cement. The specimens were cast in 50 x 50 x 50 mm cube for compressive strength test and 25x25x250 mm size for drying shrinkage. The fineness of ceramic powder used is less than 45µm. The developments of compressive strength were studied for all samples. It is found that the increases replacement cause growing strength of samples containing homogenous ceramic waste. The shrinkage value of ceramic mortar was reduced by 16% compared to OPC mortar thus, shows better performance in restraining the shrinkage deformation of the mortar. Furthermore, with replacing cement and natural fine aggregates by ceramic powder and ceramic fine aggregates reduces the usage of natural resources and minimizes the landfills problem.